100 Years Later, What Is New in Glycerol Bioproduction?. Issue 8 (August 2020) - Semkiv, Marta V.; Ruchala, Justyna; Dmytruk, Kostyantyn V.; Sibirny, Andriy A.
Abstract : Industrial production of glycerol by yeast, which began during WWI in the so-called Neuberg fermentation, was the first example of metabolic engineering. However, this process, based on bisulfite addition to fermentation liquid, has many drawbacks and was replaced by other methods of glycerol production. Osmotolerant yeasts and other microorganisms that do not require addition of bisulfite to steer cellular metabolism towards glycerol synthesis have been discovered or engineered. Because the glycerol market is expected to reach 5 billion US$ by 2024, microbial fermentation may again become a promising way to produce glycerol. This review summarizes some problems and perspectives on the production of glycerol by natural or engineered eukaryotic and prokaryotic microorganisms. Highlights: Glycerol is an important feedstock for the food, pharmaceutical, and other industries. Wild-type Saccharomyces cerevisiae produces significant amounts of glycerol from glucose after the addition of steering agents (Neuberg fermentation), whereas genetically modified S. cerevisiae strains can synthesize glycerol without steering agents under either aerobic or anaerobic conditions. Osmotolerant yeasts produce significant amounts of glycerol aerobically under hyperosmotic conditions, and can be used for industrial glycerol production. Microalgae and cyanobacteria can produce glycerol directly from atmospheric CO2, but this process has not yet been implemented industrially.